Uplift response of irregular shape anchor in sand - Niroumand, Hamed (Springer, 2014)
An investigation into the uplift response of irregularly shaped anchors in sand is described. Factors investigated in relation to the load-displacement response are sand density and embedment ratio. The results are presented based on experimental tests in this paper. The main aim of the study is to obtain validation between breakout factor and uplift load of an irregularly shaped anchor. The irregularly shaped anchor is a state-of-the-art in anchor systems and does not need any grouting or excavation for installation in comparison to conservative anchor systems. Laboratory model tests were conducted using an irregularly shaped anchor system. The anchor was embedded with an embedment ration ranging between 1 and 7. Two types of sand packing were employed, namely loose and dense compaction. Two dimensional tests to view the failure patterns were done that demonstrated patterns showing good agreement with Balla's [5] findings for anchor plates. The breakout factor shows an increment with embedment ratio.